Iowa Birdline update, January 22, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for January 22, 1990. Highlights of the update include sightings of Merlins, Short-eared Owls, and Common Redpolls. Also of note were observations of several Falcons as well as a report from Red Rock Dam of an estimated 5000 Ducks, 300 Canada Geese, and 35 Bald Eagles. Epson - sheet feed/flatbed